Hubungan Konsumsi Minuman Berpemanis (Sugar Sweetened Bevereges) dalam Kemasan terhadap Kadar Gula Darah pada Remaja SMA di Kecamatan Tuban - Rintan Elawati; Lilia Faridatul Fauziah (Inovasi Kesehatan Global, 2026)
The increased intake of packaged sugar-sweetened beverages among adolescents may affect health status, particularly blood glucose levels, as their high added sugar content can disrupt glucose metabolism when consumed excessively. This study aimed to examine the relationship between the consumption of packaged sugar-sweetened beverages and blood glucose levels among high school students in Tuban District. A quantitative approach with a cross-sectional design was employed, involving 2,092 students from four schools. The sample was selected using a stratified random sampling technique. Data on beverage consumption were collected using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), while blood glucose levels were measured using a glucometer. Data analysis was performed using the Spearman Rank correlation test with SPSS version 24. The results indicated a significant relationship between the consumption of packaged sugar-sweetened beverages and blood glucose levels among high school students in Tuban District (p = 0.000). These findings suggest that higher consumption levels are associated with higher blood glucose levels in adolescents.